Lifetime exposure to ultraviolet radiation and the risk of multiple sclerosis in the US radiologic technologists cohort study. (July 2019) - Gallagher, Lisa G; Ilango, Sindana; Wundes, Annette; Stobbe, Gary A; Turk, Katherine W; Franklin, Gary M; Linet, Martha S; Freedman, D Michal; Alexander, Bruce H; Checkoway, Harvey
Background: Low exposure to ultraviolet radiation (UVR) from sunlight may be a risk factor for developing multiple sclerosis (MS). Possible pathways may be related to effects on immune system function or vitamin D insufficiency, as UVR plays a role in the production of the active form of vitamin D in the body. Objective: This study examined whether lower levels of residential UVR exposure from sunlight were associated with increased MS risk in a cohort of radiologic technologists. Methods: Participants in the third and fourth surveys of the US Radiologic Technologists (USRT) Cohort Study eligible ( N  = 39, 801) for analysis provided complete residential histories and reported MS diagnoses. MS-specialized neurologists conducted medical record reviews and confirmed 148 cases. Residential locations throughout life were matched to satellite data from NASA's Total Ozone Mapping Spectrometer (TOMS) project to estimate UVR dose. Results: Findings indicate that MS risk increased as average lifetime levels of UVR exposures in winter decreased. The effects were consistent across age groups <40 years. There was little indication that low exposures during summer or at older ages were related to MS risk. Conclusion: Our findings are consistent with the hypothesis that UVR exposure reduces MS risk and may ultimately suggest prevention strategies.